Learning to listen strategically: Developing a listening comprehension strategies questionnaire for learning English as a global language. (December 2021) - Wakamoto, Natsumi; Rose, Heath
Abstract: In light of recent developments in the field of language learning strategies, this study aimed to validate a novel instrument to measure listening strategies of L2 learners of English. Items for a questionnaire were adapted from existing sources, generated from qualitative interviews with 34 learners, and created by the researchers themselves based on theoretical developments in self-regulation and English as a lingua franca. Validation involved a process of exploratory factor analysis with 120 learners and confirmatory factor analysis with a total pool of 255 learners of English in a university in Japan. A three-factor model emerged of cognitive strategies, metacognitive strategies, and practice (self-regulation) strategies. Multiple regression revealed that the model of listening strategies was a significant predictor of listening comprehension, as measured by the listening component of the Test of English for International Communication . However, only the 'practice (self-regulation)' factor was an independent significant predictor. The results suggest that self-regulation is a robust construct of strategic behaviour. It also reveals several items related to the use of English as a lingua franca as part of this factor, such as applying strategies to communicate with interlocutors of varying proficiencies and accents.